FINANCING OF THE AGRICULTURE IN SERBIA: STATE AND PROSPECTS - Jolović, Ana; Njegovan, Zoran; Čavlin, Miroslav (Economics of Agriculture, 2014)
Serbian agriculture has a relatively poor performance through the decades. One of the main factors is inadequate financing system for such purposes in spite of numbered financial institutions and financial sources. Especially the financial resources and its lending have a poor performance in primary production of farmers and agricultural SMEs, much poorer than in other cases and economy sectors. Governing the research concerning state and perspectives of agriculture financing in Serbia, the authors has formulated the goal to examine and determine the main factors that are shaping financing sector performance and its involvement in the business of agriculture. Also the goal was to recognize the main tendencies in the sphere of financing the agriculture as well to point the connection and interrelation between financing sector and government efforts to put much more efforts to agricultural development and institution building concerning financing at the first place.